Wet oxidation of thermochemical aqueous effluent utilizing char catalysts in microreactors. (1st June 2022) - Tews, Iva J.; Terrell, Evan; Mood, Sohrab Haghighi; Garcia-Perez, Manuel
Abstract: Production of bio-oil or biocrude from thermochemical processes such as pyrolysis and hydrothermal liquefaction (HTL) respectively, is considered a promising path for the production of alternative fuels and chemicals. However, these technologies create an aqueous phase byproduct contaminated with high concentrations of organic compounds. Traditional wastewater technologies rely on biological processing which is not resistant to the toxic levels of organic compounds present. Wet oxidation of aqueous phase byproducts is a promising processing alternative for such a dilute stream and a potential production pathway for value-added products such as acetic acid. Wet oxidation was carried out at near ambient temperature (75–90 °C) and atmospheric pressure in the presence of a hydrogen peroxide oxidant and a char catalyst activator on three individual aqueous phases. The three aqueous phases were thoroughly analyzed by total organic carbon (TOC), chemical oxygen demand (COD), Total Phenol, Total Acid Number, and individual constituents via gas chromatography with mass spectroscopy (GCMS). HTL aqueous phases were quite similar in every regard as can be seen by their COD of 44.8 and 41.5 g O2 /L respectively. The pyrolysis aqueous phase was much more complex in nature with a 10X higher COD of 364.5 g O2 /L. This was validated by ICRMS analysis which revealed the more complex molecules not visible by regular mass spectrometry. All the tests were conducted with a cellulose-based char catalyst doped with Nitrogen and Iron Oxide. The experiments were carried out in a microscale-based continuous reactor due to its superior continuous performance and reduction of transport limitations. Oxidation to small molecular weight compounds such as acetic acid was achieved with final products containing between 0.555 and 5.04 mg acetic acid/g liquid effluents. Our results confirm that wet oxidation is a promising process for the processing of aqueous effluents from biomass thermochemical conversion processes. Graphical abstract: Image 1 Highlights: Thermochemical conversion aqueous effluents are rich in organic molecules. Wet oxidation with H2 O2 shows promise for reducing the toxicity of these effluents. Microreactors with FeO- and N-doped char catalyst are utilized for wet oxidation. Hydrothermal liquefaction (HTL) derived oligomers have broader molecular weight. Fast pyrolysis oligomers are more recalcitrant than HTL to wet oxidation with H2 O2 .